Another way is to create a right triangle where ** csc(x)** is equal to

**. To do this, make**

*x***one of the non-right angles, the hypotenuse**

*θ***, and the side opposite**

*x***equal to**

*θ***. This makes**

*1***= x, and therefore the**

*csc(θ)*

*csc*^{-1}

**.**

*(x) = θ*Then use the **Pythagorean Theorem** to get the remaining side (which will be the adjacent to ** θ**). This side will be

*√(x*^{2}

**. Then**

*- 1)*

*cos(csc*^{-1}

*(x))*

*= cos(θ) = √(x*^{2}

**.**

*- 1)/x*